2019
DOI: 10.1136/bmjopen-2019-029114
|View full text |Cite
|
Sign up to set email alerts
|

Temporal trends in the prevalence and causes of visual impairment in the South Indian state of Telangana: a population-based cross-sectional study

Abstract: ObjectivesTo investigate the temporal trends in the prevalence and causes of visual impairment (VI) in South India.DesignPopulation-based cross-sectional studies conducted during the years 2011–2012 and 2017 using identical study methods and in geographical locations are compared. The L V Prasad Eye Institute established services in Khammam and not in Warangal district after the 2011–2012 study.SettingKhammam and Warangal districts in Telangana, India.ParticipantsIn total, 5357 participants aged ≥40 years were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 20 publications
2
14
0
Order By: Relevance
“…The clinical eye examination protocol is described in our previous publications. [ 14 13 14 15 16 17 ] After collecting personal and demographic information such as age, gender, education, occupation, and residential district, the awareness questionnaire was administered in the local language (Telugu) by trained field investigators and followed by clinical examination. All participants had distance and near visual acuity assessment and comprehensive eye examinations.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The clinical eye examination protocol is described in our previous publications. [ 14 13 14 15 16 17 ] After collecting personal and demographic information such as age, gender, education, occupation, and residential district, the awareness questionnaire was administered in the local language (Telugu) by trained field investigators and followed by clinical examination. All participants had distance and near visual acuity assessment and comprehensive eye examinations.…”
Section: Methodsmentioning
confidence: 99%
“…A large population-based cross-sectional study using the rapid assessment of visual impairment (RAVI) methodology was conducted in two large districts in Telangana State, India in 2017. [ 14 ] In the earlier publications from this study, prevalence and temporal trends in vision impairment in these regions were reported. [ 14 15 ] As a part of this study, awareness of common eye conditions was assessed using a validated questionnaire.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Our previous research reported a higher prevalence of visual impairment for distance in Warangal, which has continued to remain higher in subsequent studies. 27 An improvement in spectacles coverage (%) for distance vision was reported in Khammam district. 26 There is no comparative data available for NVI in these districts.…”
Section: Discussionmentioning
confidence: 95%
“…13 Neither the prevalence of CBS nor the presence of visual hallucinations is known from community-based population studies in India. As part of the survey of a larger epidemiological study 14 conducted during February-June 2017 to determine the prevalence of visual impairment in Khammam and Warangal districts in Telangana, India, we specifically aimed to screen for visual hallucinations and to determine its associations with clinical and demographic parameters.…”
mentioning
confidence: 99%